Windows on the African past : current approaches to African archaeobotany - Fahmy, Ahmed G.; Kahlheber, Stefanie.; D'Andrea, Angela Catherine. (Reports in African archaeology ;, 2011)
"Archaeobotany has significantly increased our knowledge of the relationships between humans and plants throughout the ages. As is amply illustrated in this volume, botanical remains preserved in archaeological contexts have great potential to inform us about past environments and the various methods used by ancient peoples to exploit and cultivate plants. This volume presents the proceedings of the 6th International Workshop on African Archaeobotany (IWAA) held at Helwan University in Cairo, Egypt, on 13 - 15 June 2009. Studies presented herein clearly illustrate that African archaeobotany is a dynamic field, with many advances in techniques and important case studies presented since the first meeting of IWAA held in 1994. Authors have employed classical and new archaeobotanical techniques, in addition to linguistics and ethnoarchaeology to increase our knowledge about the role of plants in ancient African societies. This book covers a wide range of African countries including Egypt, Ethiopia, Libya, Nigeria, South Africa, and the Canary Islands. It is of interest to archaeobotanists, archaeologists, historians, linguists, agronomists, and plant ecologists." -- Publisher's description.